1998
DOI: 10.1021/es970991p
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Using an Airborne Biosensor

Abstract: There is no current method for remote identification of aerosolized bacteria. In particular, such a capability is required to warn of a biological warfare attack prior to human exposure. A fiber optic biosensor, capable of running four simultaneous immunoassays, was integrated with an automated fluidics unit, a cyclone-type air sampler, a radio transceiver, and batteries on a small, remotely piloted airplane capable of carrying a 4.5-kg payload. The biosensor system was able to collect aerosolized bacteria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 10 publications
(16 reference statements)
0
38
0
Order By: Relevance
“…During development of a portable remotely operated fiber optic biosensor system for detecting aerosolized bacteria (19), research carried out by the U.S. Naval Research Laboratory revealed the potential of an immunoassay system used to sample relatively large volumes of air.…”
mentioning
confidence: 99%
“…During development of a portable remotely operated fiber optic biosensor system for detecting aerosolized bacteria (19), research carried out by the U.S. Naval Research Laboratory revealed the potential of an immunoassay system used to sample relatively large volumes of air.…”
mentioning
confidence: 99%
“…For example, the Raptor (Figure 3) is an automated fiber-optic biosensor that weighs 12 lbs, which originated in the lab of Ligler and Anderson at the Naval Research Laboratory (8). The system is based on a sandwich immunoassay in which capture antibodies are immobilized by passive adsorption onto a 4-cm fiber-optic polystyrene waveguide with a blackened distal end.…”
Section: Future Strategiesmentioning
confidence: 99%
“…A prototype system was deployed on a remotely piloted airplane that collected aerosols in flight, identified the collected bacteria, and transmitted the data to an operator (8). An alternative design by the Ligler group uses arrays of capture antibodies, thereby greatly increasing the number of simultaneous assays that are conducted by the Raptor (9).…”
Section: Corbismentioning
confidence: 99%
“…Conversely, UASs have also been used for air sampling and environmental analysis. Ligler et al (1998) integrated a biosensor system on a small and remotely piloted airplane in order to collect aerosolized bacteria in flight, identify them, and transmit the data on the ground. Nevertheless this system required human intervention for control and planning proposes.…”
Section: Introductionmentioning
confidence: 99%
“…The onboard fluorimeter (controlled by the ground station), provides real-time detection of fluorescent particles in the atmosphere. This fluorescence technique has been used by several researchers in the community for particle detection (Ligler et al, 1998;Sanders, Rodriguez, & Greenbaum, 2001;Zhang et al, 1993). The use of particle counters/sizers onboard UASs provides an excellent method of real-time identification of particles of known sizes in the atmosphere if the particles are present in large concentrations.…”
Section: Introductionmentioning
confidence: 99%